Clinical characteristics and long-term prognosis of contemporary patients with vasospastic angina: Ethnic differences detected in an international comparative study. (15th September 2019) - Sato, Koichi; Takahashi, Jun; Odaka, Yuji; Suda, Akira; Sueda, Shozo; Teragawa, Hiroki; Ishii, Katsuhisa; Kiyooka, Takahiko; Hirayama, Atsushi; Sumiyoshi, Tetsuya; Tanabe, Yasuhiko; Kimura, Kazuo; et al.
Abstract: Background: Possible ethnic differences in clinical characteristics and long-term prognosis of contemporary patients with vasospastic angina (VSA) remain to be elucidated. Methods and results: The Japanese Coronary Spasm Association (JCSA) conducted an international, prospective, and multicenter registry study for VSA patients. A total of 1457 VSA patients (Japanese/Caucasians, 1339/118) were enrolled based on the same diagnostic criteria. Compared with Caucasian patients, Japanese patients were characterized by higher proportions of males (68 vs. 51%) and smoking history (60 vs. 49%). Japanese patients more often had angina especially during the night and early morning hours, compared with Caucasians. Ninety-five percent of Japanese and 84% of Caucasian patients underwent pharmacological provocation test. Importantly, no significant differences in the patterns of coronary spasm were apparent, with diffuse spasm most frequently noted in both ethnicities. The prescription rate of calcium-channel blockers was higher in Japanese (96 vs. 86%), whereas the uses of nitrates (46 vs. 59%), statins (43 vs. 65%), renin-angiotensin-system inhibitors (27 vs. 51%), and β-blockers (10 vs. 24%) were more common in Caucasian patients. Survival rate free from major adverse cardiac events (MACE) was slightly but significantly higher in Japanese than in Caucasians (86.7 vs. 76.6% at 5 years, P < 0.001). Notably, multivariable analysis revealed that the JCSA risk score correlated with MACE rates not only in Japanese but also in Caucasian patients. Conclusion: These results indicate that there are ethnic differences in clinical profiles and long-term prognosis of contemporary VSA patients. Highlights: This is the first international study examined ethnic differences in VSA patients. Ethnic differences in clinical characteristics were present in the contemporary era. The MACE-free survival rate was slightly but significantly lower in Caucasians. The JCSA risk score was useful to predict the occurrence of MACE in both ethnics.